Kinetics of transesterification of Madhuca Indica oil over modified zeolites: biodiesel synthesis - Pratap, SR; Shamshuddin, SZM; Thimmaraju, N; Shyamsundar, M; Reena, SS (Bangladesh Journal of Scientific and Industrial Research, 2015)
In this article production of biodiesel from Madhuca indica oil (MI-oil) containing high % of free fatty acids (FFA) by transesterification process with methanol over basic zeolites such as NaY loaded with 5-25% KOH is presented. The zeolites were characterized by PXRD, BET and CO2-TPD methods prior to their catalytic activity studies. Optimization of reaction conditions for transesterification was conducted in order to get highest possible yield of biodiesel. 1HNMR and FTIR analysis confirms the conversion of MI-oil to biodiesel. The physico-chemical properties of MI-biodiesel were found to be comparable with that of the standard biodiesel. The NaY and KOH/NaY zeolites were found to be efficient and reusable catalysts without much loss of their catalytic activity when used for several times in biodiesel production. Bangladesh J. Sci. Ind. Res. 50(4), 271-278, 2015